KETERKAITAN SELF REGULATION DENGAN FEAR OF MISSING OUT PADA REMAJA SEKOLAH MENENGAH - Armilyana, Yanti; Astuti, Farida Herna; Rayani, Dewi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT The use of social media in daily life has psychological impacts on students, one of which is Fear of Missing Out (FOMO), defined as the feeling of anxiety about missing information or activities experienced by others on social media. This condition has the potential to increase anxiety, making strong self-regulation skills necessary for students to control their social media usage behavior. This study aims to analyze the relationship between self-regulation and Fear of Missing Out among eleventh-grade students of SMA Nurul Falah Perina in the 2023/2024 academic year. The study employed a quantitative approach with a correlational research design. The sample consisted of 20 students selected using a total sampling technique. Data were collected through a questionnaire as the primary instrument and analyzed using the Product Moment correlation formula. The results of the analysis showed a negative relationship between self-regulation and FOMO, with a correlation coefficient (r) of -0.746 at a 5% significance level (p < 0.05). These findings indicate that the higher the students' self-regulation ability, the lower the level of FOMO experienced. Therefore, self-regulation plays an important role in minimizing students' tendency toward FOMO. ABSTRAK Penggunaan media sosial dalam kehidupan sehari-hari memberikan dampak psikologis bagi siswa, salah satunya adalah Fear of Missing Out (FOMO), yaitu perasaan khawatir tertinggal informasi atau aktivitas orang lain di media sosial. Kondisi ini berpotensi meningkatkan kecemasan sehingga diperlukan kemampuan self regulation yang baik agar siswa mampu mengendalikan perilaku penggunaan media sosial. Penelitian ini bertujuan untuk menganalisis hubungan antara self regulation dengan Fear of Missing Out pada siswa kelas XI SMA Nurul Falah Perina Tahun Pelajaran 2023/2024. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional. Sampel penelitian berjumlah 20 siswa yang ditentukan menggunakan teknik total sampling. Data dikumpulkan melalui angket sebagai instrumen utama dan dianalisis menggunakan korelasi Product Moment. Hasil analisis menunjukkan adanya hubungan negatif antara self regulation dan FOMO dengan koefisien korelasi (r) sebesar -0,746 pada taraf signifikansi 5% (p < 0,05). Temuan ini menunjukkan bahwa semakin tinggi kemampuan regulasi diri siswa, semakin rendah tingkat FOMO yang dialami. Dengan demikian, self regulation berperan penting dalam meminimalkan kecenderungan FOMO pada siswa.